The Possible Mechanistic Basis of Individual Susceptibility to Spike Protein Injury - Matthew Halma; Paola Vottero; James Thorp; Tina Peers; Jack Tuszynski; Paul Marik (Advances in Virology)
Injury from spike protein, whether induced by COVID-19 infection or vaccination, constitutes a significant health concern for numerous individuals. Considerable heterogeneity exists in individual responses to both COVID-19 infection and vaccination, despite the latter being principally more controlled and consistent than the wide variety of infection circumstances. This review explores the possible mechanisms by which the spike protein contributes to cellular and systemic damage, highlighting the importance of understanding these processes for developing effective diagnostics and treatments.